Policing the Victorian Town - Taylor, D. author. aut Link
XV, 237 p.
Keywords: The book looks at the development of policing in a town noted for its high levels of crime. Through a detailed study of policing and police work over the period c. 1840-1914 it shows how the turbulent community of the early Victorian years was turned into a policed society by the end of the century.